2017
DOI: 10.1097/pec.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Torsion Pain Honeymoons

Abstract: A subset of testicular torsion patients report resolution of their initial severe pain that is followed by variable periods of hours to days of reduced or absent pain. Other patients report only mild pain that is described as gradual in onset. Because of delayed initial presentations or less than timely returns for secondary evaluation, these pain honeymoons may be partially responsible for poor clinical outcomes of the torsed spermatic cords and ischemic testicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…One case report highlighted a delayed TT diagnosis in a patient who was assessed for neurological deficits due to the absence of pain [11]. Another study focused on TT pain, describing the resolution of pain as the "honeymoon period" [9]. Equally, five of our patients reported reduced pain intensity or relief.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…One case report highlighted a delayed TT diagnosis in a patient who was assessed for neurological deficits due to the absence of pain [11]. Another study focused on TT pain, describing the resolution of pain as the "honeymoon period" [9]. Equally, five of our patients reported reduced pain intensity or relief.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, some adolescents experience sexual shyness, leading them to conceal their scrotal complaints and instead report abdominal or inguinal pain, along with other associated symptoms. These patients later admitted that they did not understand the importance of discussing scrotal pain and changes with their families and physicians, often due to feelings of embarrassment [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Scrotal pain is a well-known complaint in acute pediatric male patients. The symptom can be caused by a multitude of clinical conditions and therefore present a diagnostic challenge [ 1 , 2 ]. Testicular torsion is of particular interest as it may lead to the loss of a testicle if not treated promptly by surgical decompression [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classically, TT pain is described as rapid in onset, instantaneously severe, and often accompanied by nausea and vomiting. 1 , 2 A Nigerian study found that, globally, 1 in 4000 males below 25 years of age is affected annually. This study found that TT contributes to male infertility, accounting for 5.8% of testicular insufficiency.…”
Section: Introductionmentioning
confidence: 99%